The Elementary School Students ability to read with Online Methods in the Covid 19 Pandemic era (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The process of learning online makes the education has the current condition concerning. The problems occur at the Elementary School students in grades 1 and 2 is in the reading introduction stage because not all elementary school students attend kindergarten, but they have to take online schools that cannot meet their teachers in person. The students should be guided by the teacher to learn spelling and counting, could not be realized. The impact for the elementary school students in grades 1 and 2 is cannot read, even they have not memorized the alphabet completely. This is a small thing that is not visible to the naked eye but becomes a big problem in the field of education. The training and guidance for elementary school students can achieve the goal of the concepts of the 2021 KKM program, and  they are not only good at reading, but they are familiar with digital literacy which has developed very rapidly in the globalization era.